The Efficacy of Zinc Gluconate Supplementation in the Improvement of Malnutrition Indices and Skin Abnormalities in Hemodialysis Patients: A Randomized Clinical Trial - Mohammad Tavassoli; Shahrzad Shahidi; Gholamreza Askari; Naser Tavakoli; Cain C. T. Clark; Mohammad Hossein Rouhani (International Journal of Preventive Medicine)
Background: Hemodialysis patients often suffer from several complications such as malnutrition and skin abnormalities. We hypothesized that zinc supplementation may improve these complications. The aim of the present study was to examine the effects of zinc gluconate supplementation on malnutrition and skin abnormalities. Methods: In this parallel randomized, double-blind, clinical trial, patients in the zinc group received 210 mg zinc gluconate (equivalent to 30 mg elemental zinc) per day. Skin abnormalities (i.e. xerosis and pruritus), body composition, anthropometric variables, handgrip strength, and appetite (including hunger, fullness, desire to eat, and prospective food consumption) were measured at the beginning and end of the study. Results: Eighty-seven hemodialysis patients were randomly assigned to the zinc (n = 44) or placebo (n = 43) group for 12 weeks, After this period, 75 patients (N = 38 in the zinc group and 37 in the placebo group) remained in the study. In this study, no specific side effects of zinc supplementation were observed and twelve participants were lost to follow-up (n = 6 in each group) because of migration, kidney transplantation, death, dialysis access infection, and personal reasons. Zinc supplementation had beneficial effects on hunger) 95% CI: 9/55 (3/67-15/42)), desire to eat) 95% CI: 7/03 (1/82-12/24)), and prospective food consumption) 95% CI: 3/46 (0/3-14/1)) compared with placebo. Also, zinc improved pruritus) 95% CI: −0/52 (−0/82 to − 0/22)). We observed no changes in body composition, anthropometric variables, handgrip strength, and xerosis in the zinc group compared with the placebo. Conclusions: This randomized clinical trial showed that zinc supplementation yielded beneficial effects on appetite and pruritus in hemodialysis patients.